Comparison of Hevea Rootstocks and predictions of genetic parameters - Valois, Afonso C.C.; Pinheiro, Eurico; Conceição, Heraclito E.O.; Silva, Maria N.C. (Pesquisa Agropecuaria Brasileira, 2014)
Half-sib progenies obtained from 5 different clones were compared for their merits as rootstocks in nursery also including a study of correlation between each pair of the following variables: plant height, number of leaf flushes and stem diameter at 5 cm above ground. Data were taken at the age of 12 months, in a randomised block experiment with 4 replications, where 10 competitive plants were chosen for the measurements. The results showed that seedlings from IAN 717 and IAN 873, among the clones studied, must be preferably chosen as a source of seed rootstocks. Fx 3899 gave the poor results. Plant height and girth appear to be the best pair of correlated characters. The low heritability of the 3 characters studied indicate that they are highly dependent on enviromental conditions.